2013
DOI: 10.1124/mol.113.087809
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Cytoprotective Responses to Sigma1 Ligand–Induced Endoplasmic Reticulum Stress

Abstract: The Sigma1 receptor (Sigma1) is an endoplasmic reticulum (ER) integral membrane protein that is highly expressed in a number of cancer cell lines. Small molecule compounds targeting Sigma1 (Sigma1 ligands) inhibit cancer cell proliferation and induce apoptotic cell death in vitro and inhibit tumor growth in xenograft experiments. However, the cellular pathways activated by Sigma1 protein-ligand interaction are not well defined. Here, we find that treatment with some Sigma1 ligands induces ER stress and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…Cell lysis, protein extraction, SDS-PAGE, and immunoblotting were performed as described previously (13), with a few modifications. The Luminata Western HRP Substrate chemiluminescence kit (Millipore) was used to reveal immunoblotted proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lysis, protein extraction, SDS-PAGE, and immunoblotting were performed as described previously (13), with a few modifications. The Luminata Western HRP Substrate chemiluminescence kit (Millipore) was used to reveal immunoblotted proteins.…”
Section: Methodsmentioning
confidence: 99%
“…However, emerging evidence from our laboratory and others (9, 11) suggest that Sigma1 may in fact function as a novel molecular chaperone or a scaffolding protein in cancer cells. We have found that Sigma1 is involved in aspects of cancer cell protein homeostasis including protein synthesis, folding, transport, and degradation (12, 13). …”
Section: Introductionmentioning
confidence: 99%
“…In vitro radio-ligand binding assays using membranes from MDA-MB-468 cancer cells, which express Sigma1 11,28,29 provided confirmation of Sigma1 binding affinity for our new hybrid analogs compared to IPAG and haloperidol (Table 1). The hybrids 1 , 4 , 5 , 6 all demonstrated reasonable affinity to Sigma1 with about a 5–10-fold decrease in binding affinity compared to IPAG.…”
mentioning
confidence: 74%
“…Sigma1 is highly expressed in prostate cancer cells and RNAi-mediated knockdown of Sigma1 results in tumor growth inhibition. 11 Upon profiling known Sigma1 inhibitors for their ability to affect Sigma1 mediated translational repression 10 and ER homeostasis pathways, 11 we identified IPAG (1-adamantan-1-yl)-3-(4-iodophenyl)guanidine) and the anti-psychotic drug, haloperidol, as potent inhibitors of Sigma1-mediated AR signaling, protein homostasis, as well as inhibitors of cancer cell proliferation and growth. 10,11 In an effort to create new composition of matter for intellectual property protection, and to provide a new series of Sigma1 compounds for lead optimization, we utilized a hybrid pharmacophore approach to identify novel Sigma1 compounds.…”
mentioning
confidence: 99%
“…While autophagy is found to be an active process in the RPE in vivo [72], evidence from AMD donors indicates a decline of autophagic flux in the RPE [73]. Although not yet specifically investigated in RPE cells in vivo, S1R has been reported to influence autophagy in vitro [31, 32, 74]. A possible protective role of the S1R via autophagic regulations in RPE cells needs to be further determined experimentally.…”
Section: Functions Of S1r In the Retinamentioning
confidence: 99%